The destruction and reconstruction of Aleppine 'Ajami rooms of Jdaydeh's Houses' - Alafandi, Rami; Abdul Rahim, Asiah (Humanities and Social Sciences Review, 2017)
Aleppo is the commercial capital of Syria, the second most significant city after Damascus, Syria's political capital. Aleppo has a long history, extending from the third millennium BC to the Islamic era. The remains are monuments to these great civilizations. Jdaydeh is one of the historic neighbourhoods in Old Aleppo City, noted for its winding narrow alleys and richly decorated houses from the Ottoman period. These houses belonged to the Aleppine bourgeoisie, who creatively decorated them. This paper will focus on nine houses (Wakil, Dallal, Balet, Sader, Ghazaleh, Kebbe, Ajek-Pash, Zamria and Basil) that date back to17th and 19th centuries and have unique examples of the polychrome wood decorations that known as `ajami, which were documented in 2006 by the first author. Since 2012 much of Syria's architectural heritage has been destroyed due to the conflict in Syria. In Aleppo, the losses in both ancient and modern parts of the city have been tremendous. Some traditional houses have been damaged and some of the `Ajami panels have been stolen. This research employs a historical and descriptive approach to document the history of each house with the `ajami, determine the location of the `ajami rooms or panels of each house, and investigate the current situation of the houses and rooms. This paper also will propose the plan for reconstruction with some recommendations to restore the traditional houses in Aleppo for future use.